4s-4g=5g

Simple and best practice solution for 4s-4g=5g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4s-4g=5g equation:


Simplifying
4s + -4g = 5g

Reorder the terms:
-4g + 4s = 5g

Solving
-4g + 4s = 5g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-5g' to each side of the equation.
-4g + -5g + 4s = 5g + -5g

Combine like terms: -4g + -5g = -9g
-9g + 4s = 5g + -5g

Combine like terms: 5g + -5g = 0
-9g + 4s = 0

Add '-4s' to each side of the equation.
-9g + 4s + -4s = 0 + -4s

Combine like terms: 4s + -4s = 0
-9g + 0 = 0 + -4s
-9g = 0 + -4s
Remove the zero:
-9g = -4s

Divide each side by '-9'.
g = 0.4444444444s

Simplifying
g = 0.4444444444s

See similar equations:

| 2x-10=3y+9 | | -12.20+-6.01= | | 7-5[4-2y-5]= | | 7x+2+8x=32+5x | | 10+y=11 | | 16x^3+54= | | 0.35x=49 | | y-3=2.5(x+1) | | b^2-2b-8=5 | | 19.21-3.06= | | -0.4=V-5 | | (8a+7c)(8a-7c)= | | -0.4=-5V | | 2a^2-ab-3b^2=0 | | -6p-(3p-4)=2p-7 | | 5a^3b-45ab^3= | | 32-7y=11 | | x+x+1+x+2=3 | | k^2-6k-9=0 | | 144b^2-36=0 | | 7-3x=-4(2+x) | | 140+25m=400 | | 2(x-4)+3=5x | | .002x^3-.2x^2-1800=0 | | 35y-42+12y+20= | | -(k+2)=-3k-7 | | 20-9y^2=0 | | 6x=8x+30 | | 12-2(2x+10)=2 | | 36+12y=56 | | 16=6y-8 | | 3(n-5)=0 |

Equations solver categories